An investigation of the absolute circular polarization in radio pulsars - Karastergiou, A; Johnston, S (2004)
In most pulsars, the circularly polarized component, Stokes $V$, is weak in the average pulse profiles. By forming the average profile of $|V|$ from single pulses we can distinguish between pulsars where $V$ is weak in the individual pulses and those where large $V$ of variable handedness is observed from one pulse to the other. We show how $|V|$ profiles depend on the signal-to-noise ratio of $V$ in the single pulses and demonstrate that it is possible to simulate the observed, broad distributions of $V$ by assuming a model where $|V|$ is distributed around a mean value and the handedness of $V$ is permitted to change randomly. The $|V|$ enhanced profiles of 13 pulsars are shown, 5 observed at 1.41 GHz and 8 observed at 4.85 GHz, to complement the set in Karastergiou et al. (2003b). It is argued that the degree of circular polarization in the single pulses is related to the orthogonal polarization mode phenomenon and not to the classification of the pulse components as cone or core.